Effects of coping on nurses' mental health during the COVID‐19 pandemic: Mediating role of social support and psychological resilience - Ying Xu; Qing‐Xiang Zheng; Xiu‐Min Jiang; Sheng‐Bin Guo; Yu‐Lan Kang; Yu‐Ping Lin; Gui‐Hua Liu (Wiley, 2023)
Abstract Background Fighting against the COVID‐19 pandemic, front‐line nurses were under unprecedented psychological pressure. Therefore, it is necessary to promptly evaluate the psychological status of nurses during the COVID‐19 epidemic period. Aim To investigate nurses' mental health during the COVID‐19 pandemic, and to test the mediating role of social support and psychological resilience between coping and mental health. Design This was a descriptive, cross‐sectional survey which used a structural equation model. Method In total, 711 registered nurses were included. All participants were invited to complete a socio‐demographic questionnaire, the general health questionnaire, the trait coping style questionnaire, the perceived social support scale and the Conner-Davidson Resilience scale. Results In total, 50.1% nurses had high risk of mental health. Positive coping positively affected social support and psychological resilience, while it negatively affected mental health. Negative coping negatively affected social support and psychological resilience, while it positively affected mental health. Social support positively affected psychological resilience, while it negatively affected mental health. In addition, social support mediated coping and psychological resilience, and coping and mental health. Moreover, psychological resilience negatively affected mental health, and it mediated coping and mental health.